SYNTHESIS AND POLYMERIZATIONS OF N-(TERT-BUTOXY)MALEIMIDE AND APPLICATION OF ITS POLYMERS AS A CHEMICAL AMPLIFICATION RESIST - AHN, KD; KOO, DI (AMER CHEMICAL SOC, 1994)
N-(tert-Butoxy)maleimide, t-BuOMI was synthesized as a new kind of a protected acid-labile monomer. Its radical copolymerizations were performed and the thermal deprotection behavior of its copolymers were investigated. t-BuOMI was readily copolymerized with styrene derivatives (X-SO to give copolymers, P(t-BuOMI/X-St) in high conversions. The t-BuOMI units of the tert-butyl (t-Bu) protected copolymers were converted into the N-hydroxymaleimide (HOMI) units by heating at about 280 degrees C releasing 2-methylpropene and the facile deprotection of the side-chain t-Bu groups resulted in a large polarity change in the polymer structure. The deprotected copolymers, P(HOMI/X-St) have very high glass transition temperatures higher than about 250 degrees C and showed solubilities in aqueous base solutions whereas the protected polymers are soluble only in organic solvents. Acidolytic deprotection of P(t-BuOMI/St) was observed at 130 degrees C or lower temperatures in the presence of catalytic acids. Resist solutions of P(t-BuOMI/St) containing triphenylsulfonium salts as a photoacid generator were prepared and the films were imagewise exposed to 260 nm light by a contact mode. The films were post-exposure baked at 130 degrees C and were followed by development with 2.38 wt% TMAH solution to obtain positive tone images.
Keywords: COPOLYMERS; DESIGN